Use of analgesics before and after total joint replacement in working-age Japanese patients with knee and hip osteoarthritis: A retrospective database study - Nozomi Ebata; Takashi Sakai; Hiroyuki Yamamoto; Tetsumi Toyoda; Kanae Togo; Masataka Deie (Elsevier, 2024)
Background: Patterns of analgesic use before and after total joint replacement (TJR) in patients with knee/hip osteoarthritis (OA) is not well reported. Methods: This retrospective longitudinal analysis used JMDC claims data of patients who underwent knee/hip replacement surgery from 2010 to 2019. Primary outcome was proportion of patients using analgesics pre-surgery, immediately post-surgery, and in post-surgery period. Factors affecting post-surgery analgesic withdrawal and opioid prescriptions were assessed using logistic regression. Results: Of all (N = 3168) patients, those with knee OA (91.1 %) and hip OA (82.5 %) used analgesics pre-surgery, and 96.1 % with knee OA and 84.9 % with hip OA required analgesics even 3 months post-surgery. NSAIDs were most commonly used pre- and post-surgery in both OA groups. Before surgery, 15.6 % (knee OA) and 13.7 % of patients (hip OA) used weak opioids, and 23.1 % (knee OA) and 10.5 % (hip OA) of patients continued them post-surgery. Strong opioid use was noted in 2.2 % and 1.2 % of patients pre-surgery, and 5.8 % and 3.4 % of patients post-surgery in the knee and hip OA groups, respectively. Using pre-operative oral NSAIDs (odds ratio [OR]:0.56; 95 % confidence interval [CI]:0.44-0.72) and weak opioids (OR:0.58; 95 % CI:0.38-0.87) associated with withdrawal of post-surgery analgesics in patients with hip OA, and using intra-articular hyaluronic acid pre-surgery (OR:0.45; 95 % CI:0.21-0.97) was significant in patients with knee OA. Using weak (OR:4.59; 95 % CI:3.44-6.13) and strong opioids (OR:2.48; 95 % CI:1.01-6.07) pre-surgery associated with post-operative opioid use in patients with hip OA, and weak opioid use was significant in patients with knee OA (OR:7.00; 95 % CI:4.65-10.54). Conclusion: This study reported difference in analgesic use before and after TJR, and that many patients required analgesics even 3 months after TJR surgery in Japan. Pre-operative analgesic use associated with continued use after surgery. Optimal pain management before and immediately after TJR is important to reduce post-operative analgesic use, especially opioids.